A plataforma digital khan academy no ensino de matrizes: desafios e potencialidades - Silva, Nelson Batista da (2023)
Technology is present in people's daily lives and in the school environment we see our students increasingly connected. That’s why it doesn’t make sense to continue doing everything as it was done before, the content is given by the teacher who explains the subject, gives activities to be solved and corrects. We think that in a society where techonologies are present, it is necessary to change and implement technological tools that help in the educational process. The objective of the research was to practice activities on the Khan Academy platform, seeking to work with na active methodology called gamification with the conten of matrices so that the student can devolop their ability to study autonomously and exercise the use of technologies in order to improve their knowledge in matrices in a more fun and attractive way for students. The research had as participants students from EEEFM Teófilo Paulino, located in the municipality of Domingos Martins.